Non-Pharmacological Interventions for Pregnancy-Specific Anxiety Among Pregnant Women: A Systematic Literature Review - Kania Isha Maharani; Sofwan Indarjo; Alfiana Ainun Nisa (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Pregnancy specific anxiety is one of the most common mental health problems experienced by pregnant women and may negatively affect maternal and fetal outcomes. Various non-pharmacological interventions have been developed to reduce anxiety during pregnancy; however, evidence regarding the comparative effectiveness of these interventions remains heterogeneous. This study aimed to compare the effectiveness on non-pharmacological health promotion interventions in reducing pregnancy-specific anxiety among pregnant women. This study used a Systematic Literature Review design following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline. Literature searches were conducted through PubMed, Scopus, and ScienceDirect databases for articles published between 2021-2025. A total of 16 articles met the inclusion criteria and were analyzed narratively using the JBI Critical Appraisal Tool. The findings showed that mindfulness-based interventions were the most consistently effective intervention in reducing pregnancy specific anxiety, stress, emotional distress, and fear of childbirth. Other interventions such as prenatal yoga, relaxation techniques, music therapy, antenatal education, psycological, digital interventions, and structured social support also demonstrated positive effects on maternal psycological wellbeing during pregnancy. Non-pharmacological health promotion interventions have the potential to support maternal mental health and can be integrated into antenatal care services.Keywords: pregnancy specific anxiety; pregnant women; health promotion; non-pharmacological intervention; systematic literature review